Investigating the Relationship Between Moisture Content and Dry Density on Different Gradations for Road Base Granular Materials - Arumugam, Thillai Nayagee; Aman, Muhamad Yusri; Bujang, Hazirah; Muniandy, Ratnasamy (International Journal of Integrated Engineering, 2022)
CBR in granular materials is the key technical characteristic of layers in flexible pavement. CBR value is a way to measure the material stiffness used in the pavement design procedure for the road base layer depending on the types of aggregates. Road base layers ultimate role in the flexible pavement is to spread loading evenly over the sub-grade from the loading of vehicles throughout the road's design life. Among the factors affecting the material's bearing capacity, aggregate gradations are one of the most important parameters that give a significant result. Therefore, this study was carried to evaluate the effect of different aggregate gradations namely granite, basalt, and quartzite on bearing capacity in granular materials. To further analyze the effect of upper and lower limit gradations on the bearing capacity as base course layer, a series of aggregates physical tests and strength tests (CBR) have been conducted. The physical properties test results of the selected aggregates complied with Public Works Department (PWD) Road Work Specifications (2008) as specified and for the strength test. California Bearing Ratio (CBR) under controlled density and moisture for soaked and un-soaked conditions were performed.  For both soaked and un-soaked conditions, the samples with lower limit gradations showed higher stress values compared to upper limit gradations for all three types of aggregates. Granite showed higher CBR values for both, soaked, and un-soaked conditions, followed by basalt and quartzite at upper and lower limit gradation. Un-soaked granite samples with lower limit gradation showed 60.5% increment in strength compared to un-soaked upper limit gradation, followed by quartzite 53.6% and basalt 9.94% respectively. The results indicated that strength is highest in the lower limit gradations where the use of coarse-grained aggregates could significantly increase the strength